2019
DOI: 10.1017/s1751731119000879
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of passive immunity in dairy calves: the effectiveness of providing a supplementary colostrum meal in addition to nursing from the dam

Abstract: Failed transfer of passive immunity (FTPI) in dairy calves – which is often due to the low amount of colostrum provided within a few hours after birth – remains a crucial issue. Enabling dairy calves to nurse colostrum from their dams could be useful in increasing intake and thus avoiding FTPI, but further potential effects on the health and welfare of both calves and dams should also be considered. In this study, 107 calf-dam pairs from two Italian dairy farms were alternately assigned to one of the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…FTPI is defined as a <1.0 g/dL serum IgG concentration in 1-7 d old calves [16]. This cutoff point is questioned and higher cutoffs, such as 1.5 [26,27] or 2.0-2.5 [28] g/dL, which are more consistent with the challenges posed by the current rearing systems and related to better calf performance, are also suggested. Recently, Lombard et al [29] reviewed the cutoff points for TPI and suggested the new cutoff points based on the increasing IgG and serum total protein (STP) concentrations, which were related to a reduced morbidity risk and improved calf performance.…”
Section: Why Assess Tpi?mentioning
confidence: 99%
“…FTPI is defined as a <1.0 g/dL serum IgG concentration in 1-7 d old calves [16]. This cutoff point is questioned and higher cutoffs, such as 1.5 [26,27] or 2.0-2.5 [28] g/dL, which are more consistent with the challenges posed by the current rearing systems and related to better calf performance, are also suggested. Recently, Lombard et al [29] reviewed the cutoff points for TPI and suggested the new cutoff points based on the increasing IgG and serum total protein (STP) concentrations, which were related to a reduced morbidity risk and improved calf performance.…”
Section: Why Assess Tpi?mentioning
confidence: 99%
“…A majority of dairy calves are reared on pasteurized waste milk and milk replacers ( 148 ), and they are at higher risk suffering negative health sequalae due to FPT. Recent studies demonstrated that 2 vs 1 colostrum feedings after birth have resulted in decreased risk of FPT, reduced morbidity and improved growth rate ( 149 , 150 ). Finally, the protection from the passive immunity transferred to calves peaks 1–2 days and then starts declining.…”
Section: Passive Immune Protection Of Neonatal Calvesmentioning
confidence: 99%
“…Especially well described is the occurrence of infectious bovine diseases, e.g., mastitis. When the calves do not get enough good quality colostrum, the calves can develop microbial diseases due to inadequate passive immunity [11][12][13]. Specific microbes, e.g., Mycoplasma bovis or Staphylococcus aureus, in the colostrum provoke the mastitis [14].…”
Section: Contaminationmentioning
confidence: 99%